14 superior irrigated lowland breeding lines identified in multi-location trials in Cote d'Ivoire, Nigeria and Senegal - CGIAR Research Program on Rice (2020)
Multi-location trials were conducted at 4 trial locations (Ndiaye & Fanaye in Senegal; Mbe in Cote d'Ivoire and Ibadan in Nigeria) during the wet season of 2020. 14 lines superior to checks at two or three out of locations, were identified.